Blast Waves Cause Immune System Dysfunction and Transient Bone Marrow Failure in a Mouse Model - Bergmann-Leitner, Elke S.; Bobrov, Alexander G.; Bolton, Jessica S.; Rouse, Michael D.; Heyburn, Lanier; Pavlovic, Radmila; Garry, Brittany I.; Alamneh, Yonas; Long, Joseph; Swierczewski, Brett; Tyner, Stuart; Getnet, Derese; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Explosive devices, either conventional or improvised, are common sources of injuries during combat, civil unrest, and terror attacks, resulting in trauma and exposure to blast overpressure. A blast wave (BW), a near-instantaneous rise in pressure followed by a negative pressure, propagates through the body in milliseconds and can affect physiology for days/months after exposure. Epidemiological data show that blast-related casualties result in significantly higher susceptibility to wound infections, suggesting that there may be long-lasting immune modulatory effects from blast exposure. The mechanisms involved in BW-induced immune changes are poorly understood. We evaluated the effects of BW on the immune system using an established murine model. Animals were exposed to BWs (using an Advanced Blast Simulator), followed by longitudinally sampling for up to 14 days. Blood, bone marrow, and spleen were collected and analyzed for changes in the (1) complete blood count (CBC), (2) viability and composition of bone marrow cells (BMC) and splenocytes, and (3) systemic concentrations of regulatory, pro- and anti- inflammatory cytokines and chemokines. Our data demonstrate that BW results in transient bone marrow failure and long-term changes in the frequency and profile of progenitor cell populations. Consequential to the impact of BWs on viability and frequency of hematopoietic cells in the bone marrow, we observed effects of BW on the numbers of CBCs. In addition, dynamic changes in the concentrations of several cytokines and chemokines were observed that may contribute to dysregulation of immune response to trauma and infections. This work lays the foundation for identifying the potential mechanisms behind BW’s immunosuppressive effects. Recognition of this compromised status is crucial for the development of therapeutic interventions for infections intended to hasten the recovery time needed for wounded patients injured by explosive devices.